Multicast Stream Builder Based Video Service Using Adaptive Bitrate Streaming and Content Delivery Networks - Subramaniam Natarajan, Gowrishankar; R Krishnaveni, Dr. (International Journal of Engineering and Technology, 2026)
Currently, the delivery of multimedia content like video and live programs, not only happens via cable networks and DTH (direct to home), but are increasingly moving towards IP (internet protocol) based delivery of multimedia content. Consumers today may seek for a personalized & interactive video watching experience. MPVDs (Multi-programming Video Distributors) are increasingly switching to IP based video or any multimedia content delivery, to build an immersive video viewership base. MVPDs provide both live and on demand video services to consumers based on both subscription and transactional business models. Even though MPVDs are gaining in market share and provide a large volume of video services today, there are still several challenges that they need to overcome such as network congestion due to the downstream network bandwidth, unpredictable network loads since in most cases the MPVDs do not control the network they deliver content. Also, improving the access to network bandwidth alone will not solve the problem of network congestion, since the “core” and “aggregate” networks usually have fixed bandwidth pipes. However, in spite of several advancements in multimedia content delivery technologies, delivering best-in class video quality over IP networks, especially for live video streaming, still presents a host of challenges. Significant amongst these challenges are network delays/jitters and packet losses due to network congestion. Across any multimedia content delivery pipeline, a multimedia content streaming losses occur in the network where the content is delivered from the CDN (content delivery network) edge caches to consumer devices viz. mobile phones, tablet form factors, Smart TVs and/or STBs.Moreover, it is much more tedious and cost prohibitive to perform regular network upgrades for bandwidth expansion.MPVDs (Multi-programming Video Distributors) are increasingly switching to IP based video or any multimedia content delivery, to build an immersive video viewership base.
Keywords: Over the Top Video Streaming Service; Multi-Channel Video Programming Distributor (MVPD); content delivery networks (CDN); Multicast video streaming; network congestion.